Nutritional applications and beneficial health applications of green tea and l‐theanine in some animal species: A review. Issue 1 (8th October 2019) - Alagawany, Mahmoud; Abd El‐Hack, Mohamed E.; Saeed, Muhammad; Naveed, Muhammad; Arain, Muhammad A.; Arif, Muhammad; Tiwari, Ruchi; Khandia, Rekha; Khurana, Sandip K.; Karthik, Kumaragurubaran; Yatoo, Mohd. I.; Munjal, Ashok; et al.
Abstract: Green tea ( Camellia sinensis ) is a popular herbal plant with abundant health benefits, and thus, it has been used as a potent antioxidant for a long time. Based on the available literature, the diversity and the availability of multifunctional compounds in green tea offer its noteworthy potential against many diseases such as liver and heart diseases, inflammatory conditions and different metabolic syndromes. Owing to its bioactive constituents including caffeine, amino acids, l ‐theanine, polyphenols/flavonoids and carbohydrates among other potent molecules, green tea has many pharmacological and physiological effects. The effects of green tea include anti‐oxidative, anti‐inflammatory, anti‐arthritic, anti‐stress, hypolipidaemic, hypocholesterolaemic, skin/collagen protective, hepatoprotective, anti‐diabetic, anti‐microbial, anti‐infective, anti‐parasitic, anti‐cancerous, inhibition of tumorigenesis and angiogenesis, anti‐mutagenic, and memory and bone health‐improving activities. Apart from its utilization in humans, green tea has also played a significant role in livestock production such as in dairy, piggery, goatry and poultry industries. Supplementation of animal feeds with green tea and its products is in line with the modern concepts of organic livestock production. Hence, incorporating green tea or green tea by‐products into the diet of poultry and other livestock can enhance the value of the products obtained from these animals. Herein, an effort is made to extend the knowledge on the importance and useful applications of green tea and its important constituents in animal production including poultry. This review will be a guideline for researchers and entrepreneurs who want to explore the utilization of feeds supplemented with green tea and green tea by‐products for the enhancement of livestock production.